Language Competence in The Digital Disruption Era: A Psycholinguistic Case Study of 2-Year-Old - Prasetyo, Muhamad Agus; Kusmiatun, Ari (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract: The research aims to identify and describe competencies related to language acquisition of 2-year-old children in the digital disruption era. This research is based on the phenomenon of the times that triggered the digital disruption era to affect children's language acquisition. This research focused on a case study of a 2-year-old child's language acquisition at the phonological and morphosyntactic levels. This research design is descriptive qualitative with a theoretical approach, psycholinguistics. The subject and data source was a 2-year-old boy with the initials DBS. The data collection technique was conducted using participant and non-participant observation techniques, while the data analysis technique included condensation, display, and conclusion/verification. The research results showed: (1) DBS phonology acquisition competence consists of 9 vowel phonemes with minimal vocalic system dominance, 18 consonant phonemes including trill sounds with minimal consonantal system dominance, two diphthongs from national and foreign languages phoneme, one foreign language cluster phoneme which is replacing with the closest mother tongue phoneme; (2) DBS morphosyntactic acquisition competence is dominated by word function in the form of subject, word role in the form of actor, and word category in the form of the noun. In conclusion, the language acquisition competence of two-year-old children in the digital disruption era is quite varied from the previous era, in line with the acquisition of Javanese, Indonesian, English, and Malay lexicons.Keywords: Digital Disruption, Language Competence, Psycholinguistic, Two-Year-Old Child